Human cell based directed evolution of adenine base editors with improved efficiency - Junhao Fu (Nature Portfolio, 2021)
Application of adenine base editors (ABE) has been precluded by low activity. Here the authors show the generation of a human cell based ABE directional screening system and identification of ABE variant (NG-ABEmax-KR) exhibiting a significant increase in activity for human and mouse genome manipulation.